Efek posisi penempatan box dan jarak pengangkutan terhadap penyusutan bobot badan dan persentase penyusutan bobot badan pada ayam pedaging finisher - Muharlien Muharlien; Achmanu Achmanu; Fani Yulianto (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2011)
The research objective was to study the effect of box position and transportation distance  on body weight loss and the percentage of body weight loss on broiler finisher. The materials were 150 male chickens and 150 female chickens of broiler finisher. The research applied experimentally method was arranged in Randomyzed Block Design, with transportation distance as replication group and box position as treatment. Variable  observed were  body weight loss and percentage body weight loss. The datas analysis by ANOVA.  If there were a different between treatments, were be continued by Least Significant Difference Test. The results of experiment indicated that the higher the placement position of the front box gave body weight loss and percentage of body weight loss on both male and female broiler chickens was higher. The farther distance of transportation both in male and female broiler chickens gave body weight loss and percentage of body weight loss higher. The suggestion was in the transportation broiler placement should placed in the position of front and back of the box, should not be too high to avoid greater body weight loss. In the long-distance transport needs to be given a transit point (rest) as well as feeding and drinking to minimal effect on   body weight loss.   Keyword :  Broiler finisher, Box Position, Transportation distance, Body weight loss